The design and construction of a magnetic separator - White, Ralph Richard; Davis, Charles Earnest (My University, 1906)
Introduction: It requires no little amount of care and time to avoid the mixing of iron with brass filings in the machine shop, especially where diversified work is done on the same machines. The brass filings are quite valuable but are useless when mixed with iron since the brass filings cannot be recast in the presence of the iron filings without the iron being mixed through the casting, unmelted. It is a laborious task to separate these metals with the hands or by means of a magnet; hence the necessity of a magnetic separator in the machine shop. In designing a magnetic separator our object was that of magnetizing a rotating cylinder, thus holding the iron filings on it's surface while the brass, being non-magnetic, falls off due to gravity as the drum rotates. Everyone who has gained any knowledge of electricity has learned that when a current is passed through a coil of wire wound about a piece of magnetic material, this material will attract and hold other magnetic materials. By Plate II one can see that eighty four electro-magnets have been set into an iron hub, the design of which is represented in Plate III. If we pass a current through the coils of the magnets they will become magnetized and retain any particles of iron which might come in contact with them.
Citation: White, Ralph Richard and Davis, Charles Earnest. The design and construction of a magnetic separator. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Magnetic Separator; Blueprints; Theses